Pneumomediastinum, Pneumopericardium and Subcutaneous Emphysema Following Acute Lymphoblastic Leukemia and Chemotherapy: a Case Report - Mohammad Kajiyazdi; Amir Hossein Norooznezhad (Babol University of Medical Sciences, 2021)
Background: It is a rare cardiac malignant primary tumor that seems to derive from the same cellular line as myxomas, but the prognosis is very different. It is a rare cardiac malignant primary tumor that seems to derive from the same cellular line as myxomas, but the prognosis is very different. It is a rare cardiac malignant primary tumor that seems to derive from the same cellular line as myxomas, but the prognosis is very different. Cardiac myxosarcoma is a rare neoplasm that appears to rise from the same cellular source like myxoma. It is difficult to differentiate a myxoma tumor from a myxosarcoma tumor because of its appearance and pathology examination. Myxosercoma tumor requires surgery and chemoradiotherapy, but myxoma is treated only by surgery. Case Presentation: We describe a case of a 58-year-old patient with a left atrium myxosarcoma, presenting with congestive heart failure. Transthoracic echocardiogram (TTE) showed a large polypoid and mobile mass in the left atrium, the patient underwent cardiac surgery and the tumor was successfully extracted, and histopathological result revealed typical features of myxoma. 15 days after surgery, he underwent explorative laparatomy because of progressive GI bleeding. Laparatomy revealed extensive metastatic masses in abdomen and the pathology diagnoses was myxosaroma. Unfortunately, in spite of supportive care, the patient expired on postoperative day one. Conclusion: It is difficult to differentiate a myxoma tumor from a myxosarcoma tumor because of its appearance and pathology examination. Maybe magnetic resonance imaging can help us to achieve more data suggesting malignancy.